2006
DOI: 10.1038/sj.onc.1209832
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Nr-13 antideath activity by peptide aptamers

Abstract: Tumor cells are characterized by deregulated proliferation and resistance to proapoptotic stimuli. The Bcl-2 family of antiapoptotic proteins is overexpressed in a large number of chemoresistant tumors. Downregulation or inhibition of antiapoptotic proteins might result in the sensitization of cancer cells to chemotherapeutic agents. In the present study, we took advantage of the peptide aptamer strategy to target Nr-13, a Bcl-2 antiapoptotic protein involved in neoplastic transformation by the Rous sarcoma vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…We have been interested in the peptide aptamers (PAs) technology to target HSPB1 structure/function. Indeed, recent studies have shown that PAs can successfully modulate the activity of a wide range of intracellular proteins involved in cell growth regulation, such as cyclin-dependent kinase 2 (CDK 2) [35], epidermal growth factor receptor [36], calcineurin [37], BCL-6 [38] and Nr-13 [39]. These studies illustrate the power of phenotypic screening of combinatorial peptide libraries in order to interrogate the proteome and chart molecular regulatory networks.…”
Section: Introductionmentioning
confidence: 99%
“…We have been interested in the peptide aptamers (PAs) technology to target HSPB1 structure/function. Indeed, recent studies have shown that PAs can successfully modulate the activity of a wide range of intracellular proteins involved in cell growth regulation, such as cyclin-dependent kinase 2 (CDK 2) [35], epidermal growth factor receptor [36], calcineurin [37], BCL-6 [38] and Nr-13 [39]. These studies illustrate the power of phenotypic screening of combinatorial peptide libraries in order to interrogate the proteome and chart molecular regulatory networks.…”
Section: Introductionmentioning
confidence: 99%
“…Peptide aptamers have also been described to the DNA-binding domain and the dimerization domain of the transcription factor signal transducer and activator of transcription 3 (via epidermal growth factor receptor) causing tumor cell apoptosis (10). Recently, RNA aptamers have also been described to the Ku proteins involved in DNA repair leading to a sensitization of breast cancer cells to etoposide (11) and peptide aptamers to the BCL2 antiapoptotic protein Nr-13 (12).…”
Section: For Review)mentioning
confidence: 99%
“…The role of the scaffold is to display a conformationally constrained sequence of amino acids and to stabilize them in the cellular environment. PAs can specifically bind to and modulate the activities of a wide range of intracellular proteins, including oncogenes, transcription factors, cell cycle regulators and others (Buerger et al, 2003;Chattopadhyay et al, 2006;Nouvion et al, 2007).…”
Section: Introductionmentioning
confidence: 99%